1995
DOI: 10.1074/jbc.270.43.25850
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of the Promoter for the Chinese Hamster DNA Topoisomerase IIα Gene

Abstract: To investigate the mechanisms governing the expression of DNA topoisomerase II␣, the Chinese hamster topoisomerase II␣ gene has been cloned and the promoter region analyzed. There are several transcriptional start sites clustered in a region of 30 base pairs, with the major one being 102 nucleotides upstream from the ATG translation initiation site. Sequencing data reveal one GC box and a total of five inverted CCAAT elements (ICEs) within a region of 530 base pairs upstream from the major transcription start … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…Using promoter deletion constructs and mutated ICB consensus sites, it has been well documented that the ICBs in the topo II␣ promoter are required for optimal transcriptional activity (Hochhauser et al, 1992;Ng et al, 1995;Park et al, 1995;Herzog and Zwelling, 1997). Isaacs et al (1996) first indicated that the transcription factor complex NF-Y binds to the ICBs of the topo II␣ promoter, and this NF-Yspecific binding has been confirmed by others (Herzog and Zwelling, 1997;Wang et al, 1997), including this present report.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Using promoter deletion constructs and mutated ICB consensus sites, it has been well documented that the ICBs in the topo II␣ promoter are required for optimal transcriptional activity (Hochhauser et al, 1992;Ng et al, 1995;Park et al, 1995;Herzog and Zwelling, 1997). Isaacs et al (1996) first indicated that the transcription factor complex NF-Y binds to the ICBs of the topo II␣ promoter, and this NF-Yspecific binding has been confirmed by others (Herzog and Zwelling, 1997;Wang et al, 1997), including this present report.…”
Section: Discussionsupporting
confidence: 66%
“…Several laboratories have documented the vital role of multiple ICBs in the topo II␣ promoter for expression of the topo II␣ gene in both human and rodent cell lines (Ng et al, 1995;Herzog and Zwelling, 1997;Wang et al, 1997;Takano et al, 1999). Earlier studies from our lab have demonstrated that successive deletions of each of the five ICBs from the topo II␣ promoter results in progressively reduced promoter activity in mouse embryo fibroblast (10)1 cells and that the activity of the topo II␣ promoter is specifically inhibited by wt p53 but not by mutant p53 (Wang et al, 1997 and Table 1).…”
Section: Binding Of Transcription Factors To the Icbs Of The Topo Ii␣mentioning
confidence: 99%
“…However, the topo II␣ promoter differs from other known wt p53-suppressed genes in that it does not contain a TATA box consensus site. The topo II␣ promoter elements that do appear to play a significant role in transcription are the ICEs, of which there are five (37,40,60,63). Studies of the hamster topo II␣ promoter have shown that the ICEs are functionally important for topo II␣ promoter activity and that these sites form complexes with ICE-binding proteins (60).…”
Section: Vol 17 1997 P53 Inhibits Topoisomerase Ii␣ Expression 391mentioning
confidence: 99%
“…The topo II␣ promoter elements that do appear to play a significant role in transcription are the ICEs, of which there are five (37,40,60,63). Studies of the hamster topo II␣ promoter have shown that the ICEs are functionally important for topo II␣ promoter activity and that these sites form complexes with ICE-binding proteins (60). Recent work on the regulation of the human topo II␣ promoter in confluence-arrested cells demonstrated that the second ICE is involved in the down-regulation of topo II␣ expression (40).…”
Section: Vol 17 1997 P53 Inhibits Topoisomerase Ii␣ Expression 391mentioning
confidence: 99%
See 1 more Smart Citation